LISTENING-FIRST APPROACH AND LISTENING STRATEGIES TOWARDS SUCCESSFUL EFL LISTENING CLASSROOM - Gurendi Wiwoho (Universitas 17 Agustus 1945 Semarang, 2021)
This paper highlights the importance of listening comprehension in learning English as a foreign language (EFL). The aim of this paper is two-fold: (1) to suggest use of listening-first approach towards successful listening comprehension teaching; and (2) to propose a challenge of teaching listening strategies to help students acquire good competence in listening comprehension. It cites significant research findings in second language acquisition and reviews the concept of listening comprehension and listening strategies and their relationship language teaching and learning. Research suggests that listening is prerequisite to other language skills, speaking, reading, and writing, and listening should be the primary skill to be acquired in learning a new language. There are major reasons for applying the listening-first approach. Listening comprehension sets a foundation for the future acquisition of speaking. Emphasis on aural comprehension training, and relaxation of the requirement for oral production in the initial phase of instruction, fosters development of linguistic competence, and produces better results than those obtained through intensive oral practice. Additionally, research also suggest that listening strategy is something teachable, so that it can be taught students in such a way that they will have opportunities to choose which suits their learning capability.